The Impact of Safety Management System and Safety Risk Management Towards Aviation Safety Performance at an Airline Company - athallah saputra, fadhil; ratna wijayanti, ra. afera; gusmali, joni (LIAISON JOURNAL OF BEST, 2024)
Since the earliest days of the aviation industry via the invention of the first airplane by the Wright brothers, many risks and perils have consistently arisen to challenge human comprehension of aviation safety. Over time, there has been a concomitant increase in technological advancements aimed at assisting individuals in overcoming this challenge. The respective airline company, an esteemed Indonesian aviation company, now occupies the leading position in the aviation industry inIndonesia. They have just received a 5-star accreditation for aircraft safety during the COVID-19 pandemic. The respective airline company excels in the Indonesian aviation industry, as shown by its many certifications and honors. The respective airline company’s ownership of subsidiaries and its own group contributes to its prestigious 5-star airline reputation. The objective of this study is to determine the elements that impact the safety performance indicator, with a special emphasis on safety risk management and safety management system, at this respective airline company. This study used quantitative data in the form of a questionnaire. The questionnaire was submitted to the appropriate department of this respective airline company and all of them were deemed suitable foruse. The use of Structural Equation Modelling (SEM) provided an illustration of the results, regression weights, and model fit for the analysis of the study model. Keywords: Aviation Safety, Safety Risk Management, Safety Management System, Aviation Safety Performance Indicators